Implementasi Implementasi Gerakan 15 Menit Membaca di Lingkungan SMP Yakha Garut: Dampaknya terhadap Kesadaran Literasi - Dioka Muhammad Akbar; Winka Naida; Arya Dewo Sundara (BADAN PENERBIT STIEPARI PRESS, 2025)
This community service report evaluates the implementation of the 15-Minute Reading Movement at SMP Yakha Garut as a response to the low literacy awareness in Indonesia. Global data from UNESCO and PISA surveys show that Indonesia ranks worryingly low in literacy. The School Literacy Movement (GLS), regulated by the Ministry of Education and Culture, was introduced as a structured effort to foster a reading culture among students. This community service aims to analyze the impact of the specific literacy program implemented at SMP Yakha Garut on students' literacy awareness, focusing on its psychological, cognitive, and sociolinguistic effects. A descriptive quantitative approach is used, adopting Kirkpatrick’s evaluation framework, which includes four levels: participant reaction, learning, behavior change, and final outcomes. Data were collected through questionnaires distributed to students as respondents. The findings indicate that the consistent implementation of the 15-Minute Reading Movement, based on the habit-forming principle of making reading activities enjoyable and easily accessible, successfully increased students’ reading interest. Furthermore, there was a significant improvement in text comprehension and students' confidence in interacting with books. The success of this program highlights the importance of comprehensive school ecosystem support, from strong policies to the role of teachers as role models in implementing a literacy culture. These findings also demonstrate that school literacy programs can positively impact students’ literacy awareness and contribute to the development of a better reading culture in the future.